Implementation of Journalistic Training at Extracurricular Broadcasting “Lensa Manduta” MAN 2 Tangerang - Wahyunengsih Wahyunengsih; Syifa Awaliyah; Ainun Ilma (Comit: Communication, Information and Technology Journal, 2023)
Writing is one of the journalistic skills that have a great influence on students so they are expected to disseminate information and even express feelings to the public through written language. Journalistic media for schools is a means of information about schools, education, entertainment, and persuasion. So, with journalism training, someone will be helped in honing creativity and talent. This study aims to observe the development of journalistic insights of students through journalistic training and provide solutions to the problem of lack of journalistic insights by motivating MAN 2 Tangerang students, especially members of the Broadcasting Extracurricular Lensa Manduta to be skilled in the field of writing. The method used in this research is the descriptive qualitative method. Data collection techniques and observations that researchers use include observation by observing and recording activities carried out by the journalistic division of Lensa Manduta and interviews with the head of the journalistic division and the general chairman of Lensa Manduta. The results of this study are that the journalistic training was opened interactively, the members listened to the material presented, and were quite responsive in practice to the field. In addition, they are quite familiar with the terms in journalism, such as journals, and codes of ethics, as well as a very good understanding of news, it's just that they don't know the whole, such as the types of news consisting of hard news, soft news, and straight news. Keywords: Journalistic training, extracurricular, writing, Lensa Manduta MAN 2 Tangerang